State Fragility and the Resurgence of Military Coups in West-Africa - OLADOYIN, Anthony Mayowa; OSIMEN , Goddy Uwa; POKUBO, Ibiso Esther; OBOZEKHAI, Esther Ewenme; OLADIPO, Temidayo David (Journal of Ecohumanism, 2024)
State fragility and coups in Franco-phone West Africa constitute a worrisome political issue caused by weak leadership, instability, poverty, corruption, weak governance institutions, insurgency and terrorism, kidnapping and banditry, border porosity and high rates of military coup. The paper analysed the causes and consequences of military takeovers in West Africa and the role of regional organizations in curbing them. Secondary materials were used for data analysis. The paper concludes that the brazen-faced and audacious French imperialism in West Africa has contributed to the ongoing instability and insecurity in the subregion; creating a fertile ground for coup resurgence, which was driven by military leaders seeking to gain control and exploit the resources of the region for their own benefit. The paper thus suggests that as soon as the polity is stabilized, political power should be returned to the people in the affected States.